PENGARUH SELF-ESTEEM TERHADAP ADAPTABILITAS KARIR YANG DIMEDIASI OLEH PERCEIVED SOCIAL SUPPORT PADA KARYAWAN DI SALAH SATU PERBANKAN SYARIAH KOTA BANDA ACEH - Faizal Haris; Ade Irma Suryani (Departemen Manajemen, 2021)
This study aims to examine the effect of Self-Esteem on Career Adaptability with Perceived Social Support as a mediating variable for Employees in One of the Sharia Banking Cities in Banda Aceh. The sample used in this study was 145 employees in one of the Islamic banking in the city of Banda Aceh by using probability sampling techniques. Then, this study uses data collection tools, namely, questionnaires (questionnaire). This study uses Hierarchical Linear Modeling (HLM) as an analytical method to determine the effect of the variables involved and also use the Sobel Test for mediation testing in this study. Based on the results of the HLM analysis and Sobel Test, showing that Self-Esteem has a positive effect on Career Adaptability, Self-Esteem has a positive effect on Perceived Social Support, Perceived Social Support has a positive effect on Career Adaptability, and Perceived Social Support partially mediates the Self-Esteem on Career Adaptability.